(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Effective communication between nurses and patients is a fundamental aspect of high-quality healthcare delivery. This research examines the impact of effective nurse-patient communication on healthcare quality, considering various dimensions including patient satisfaction, adherence to treatment plans, patient safety, and clinical outcomes. A comprehensive review of literature reveals the significant role of communication skills in promoting patient-centered care, fostering trust and collaboration, and improving health outcomes. Factors influencing effective nurse-patient communication, such as verbal and non-verbal communication, active listening, empathy, cultural competence, and health literacy, are explored. Additionally, the study investigates strategies to overcome communication barriers, including language barriers, cultural differences, and health literacy levels. Findings highlight the importance of investing in communication training and resources for nurses, promoting a culture of patient-centered care, and fostering interdisciplinary collaboration to enhance healthcare quality.